Bubble Wing - Rakesh B. R. (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This study explores modifications to airfoil structures designed to reduce aircraft speed during critical situations, enabling smoother and safer emergency landings. By optimizing aerodynamic performance, the proposed design minimizes impact forces upon ground contact. The results provide a foundation for integrating advanced airfoil designs into emergency response protocols.